2008
DOI: 10.1007/s00213-008-1286-5
|View full text |Cite
|
Sign up to set email alerts
|

The glycine transporter 1 inhibitor SSR504734 enhances working memory performance in a continuous delayed alternation task in C57BL/6 mice

Abstract: Rationale Inhibition of the glycine transporter 1 (GlyT1) activity increases extra-cellular glycine availability in the CNS. At glutamatergic synapses, increased binding to the glycine-B site located in the N-methyl-D-aspartate receptor (NMDAR) can enhance neurotransmission via NMDARs. Systemic treatment of 2-chloro-N-[(S)-phenyl [(2S)-piperidin-2-yl] methyl]-3-trifluoromethyl benzamide, monohydrochloride (SSR504734), a selective GlyT1 inhibitor, is effective against social recognition impairment induced by ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 70 publications
1
33
0
Order By: Relevance
“…Similarly to these findings, we found that Org-24461 selectively increased extracellular glycine concentrations in conscious rat striatum whereas increases in serine or glutamate concentrations were not seen in the microdialysis samples. Since Org-24461 and other GlyT-1 inhibitors do not exhibit major binding affinity to most neurotransmitter receptors, elevation of glycine concentrations in the vicinity of impaired NMDA receptors may be responsible for their antipsychotic [10,11,32] and procognitive [14,33] effects. It has been shown that the GlyT-1 inhibitors glycyldodecylamide and ALX5311 reduced NMDA-induced [ 3 H]dopamine release from mouse striatal slice preparations [34,35].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly to these findings, we found that Org-24461 selectively increased extracellular glycine concentrations in conscious rat striatum whereas increases in serine or glutamate concentrations were not seen in the microdialysis samples. Since Org-24461 and other GlyT-1 inhibitors do not exhibit major binding affinity to most neurotransmitter receptors, elevation of glycine concentrations in the vicinity of impaired NMDA receptors may be responsible for their antipsychotic [10,11,32] and procognitive [14,33] effects. It has been shown that the GlyT-1 inhibitors glycyldodecylamide and ALX5311 reduced NMDA-induced [ 3 H]dopamine release from mouse striatal slice preparations [34,35].…”
Section: Discussionmentioning
confidence: 97%
“…This may have importance in the treatment of various types of endogenous psychosis characterized by hypofunctional NMDA receptors [9]. Similarly to antipsychotics, GlyT-1 inhibitors exert antipsychotic effects in a number of animal models of schizophrenia [10][11][12] and they also improve memory impairment in animal tests [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Slc6a9 plays a role in the regulation of glycine levels in NMDA receptor-mediated neurotransmission, and is used as a therapeutic target for schizophrenia [Bergeron et al, 1998; Mohler et al, 2011]. In vitro and in vivo modulation of Slc6a9 expression is associated with NMDA neurotransmission facilitation and working memory enhancement [Yee et al, 2006; Singer et al, 2009]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that compounds that elevate extracellular glycine via inhibition of GlyT-1 activity can ameliorate cognitive deficits (Liem-Moolenaar et al, 2010;Wallace et al, 2011;Nikiforuk et al, 2011;Singer et al, 2009). Therefore, the aim of our study was to determine whether a GlyT-1 inhibitor might also enhance the consequences of extinction training in subjects with cocaine self-administration histories.…”
Section: Introductionmentioning
confidence: 99%